Nghiên cứu chế tạo vật liệu nanocompozit trên cơ sở nhựa epoxy DER 331 và nanoclay. Phần 2. Nghiên cứu ảnh hưởng của hàm lượng nanoclay đến tính chất của vật liệu - Quyền, Nguyễn Công; Chương, Bùi; Yến Oanh, Đoàn Thị; Phong, Nguyễn Tiến (Vietnam Journal of Chemistry, 2015)
The effect of nanoclay on some properties of epoxy resin DER 331 was studied. The results showed that contents of nanoclay up to 8 phr do not effect on curing level of resin. With nanoclay content of 2 phr, the properties of epoxy resin have been improved. The properties of resin as tensile, flexural, compressive,  and impact  strengths, swear resistance  are increased as 30 %, 50-70 %, 40 % and 60-70 % respectively. However, the properties of epoxy resin are decreased with increasing nanoclay (above 3-5 phr) than that of original resin.